An Examination of Social Sustainability for Human Flourishing - Landrum, N.; Simaens, A.; Salgueiro, M.F. (10th Responsible Management Education Research Conference, 2023)
This communication aims to is to integrate social sustainability more prominently into the stages of corporate sustainability (Landrum, 2018). This unified model of stages of sustainability resulted from an integration of 22 micro- and macro-level stage models of environmental management, corporate social responsibility, corporate sustainability, and sustainable development. The stages, in increasing levels of sustainability strength, are: 1) Compliance sustainability; 2) Business-centered sustainability; 3) Systemic sustainability: 4) Regenerative sustainability; and 5) Coevolutionary sustainability (Landrum, 2018). Social sustainability is the most underdeveloped element of sustainability (McGuinn et al., 2020). Historical approaches toward sustainable development have relied upon a basic needs approach characterized by a reductionist analytic orientation. Haq (1995, 2008), Nussbaum (2000), and Sen (1987, 1989, 2000) propose the human development and capabilities approach that adopts a more holistic and systemic orientation to support human flourishing. Strong sustainability theory and the sustainability spectrum (Pearce, 1993) suggest that sustainability can be viewed as a gradient of progressive stages. We propose that there are also variations of social sustainability that can be viewed as progressive stages toward integration and flourishing. This research integrates prior research from multiple theoretical and disciplinary backgrounds to develop a gradient model that reflects degrees of social sustainability ranging from very weak to very strong. Thematic analysis seeks patterns and themes in the data set (Braun & Clark, 2006). Thematic analysis is then used to identify placement of sustainability schemes along the gradient. Boyer et al. (2016) and Landrum (2018) have already completed the inductive thematic analysis across texts to categorize worldviews toward social sustainability and corporate sustainability, respectively. This model can help researchers and practitioners move closer toward operationalization of social sustainability and better integration of the concept in sustainability initiatives. This is a work in progress. The first stage of research is integration of prior work into a single model. The second stage of research is to use thematic analysis to evaluate sustainability scheme documents and test alignment with the stage model. Consistent with the conference theme of sustainable and responsible management, this research integrates prior knowledge with the intent of improving the definition and inclusion of social sustainability for increased societal impact. This is a work in progress that challenges established frameworks on the integration of social sustainability. A comparison of results between this research focused on social sustainability and others focused on environmental sustainability (e.g. Landrum & Ohsowski, 2017, 2018) reveal that social sustainability, environmental sustainability, and economic sustainability are still distinct concepts. Companies’ performance in one dimension of sustainability is independent of performance in another dimension, reinforcing the need to better integrate the three dimensions, both in theory and in practice.